Kalibrasi Parameter Terhadap Debit Banjir Di Sub DAS Siak Bagian Hulu - Wibowo Suarno Putra; Yohanna Lilis Handayani; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Upper Siak watershed is increase discharge caused by the land use change. Therefore, this study is aimed to calibrate the parameters of the flood discharge in the upper siak watershed. Various hydrological modeling to calculate the flood discharge have been developed, one of them that is used in this study is the HEC-HMS (Hydrologic Engineering Center-Hydrologic Modelling System). Calibration parameters intended that the flood discharge output HEC-HMS approaching the flood discharge observation. Calibration data input is in the form of daily rainfall data, hourly discharge, and land use maps of 2012. Based on the calibration results showed that the flood discharge has a duration of 3 hours have simulated peak flow value of 70,99 m³/s while the observed peak flow amounted to 71,06 m³/s with a percent difference of 0,1% and the flood discharge duration of 6 hours have simulated peak flow value of 70,60 m³/s while the observed peak flow amounted to 71,06 m³/s with a percent difference of 0,6%.Keywords: land use change, calibration, flood discharge, HEC-HMS